Prognostic factors in children undergoing salvage surgery for bladder/prostate rhabdomyosarcoma. Issue 4 (August 2016) - Angelini, Lorenzo; Bisogno, Gianni; Alaggio, Rita; Scarzello, Giovanni; Santoro, Luisa; Zanetti, Ilaria; Scagnellato, Angela; Basso, Eleonora; D'Angelo, Paolo; Ferrari, Andrea; Castagnetti, Marco
Summary: Background: Prognostic factors have been studied in patients with rhabdomyosarcoma in general, but little is known about prognostic factors in the subgroup of patients with bladder/prostate rhabdomyosarcoma (BP-RMS) requiring salvage surgery after failure of chemotherapy ± radiotherapy to achieve local control. We reviewed the 28-year Italian experience with BP-RMS requiring salvage surgery after failure of nonsurgical management indicated by evidence of disease persistence after chemotherapy ± radiotherapy. Our hypothesis was that the same variables identified as prognostic factors in the general population with RMS could have prognostic value in this subgroup. Method: Between 1986 and 2014, 108 patients with a histological diagnosis of BP-RMS were registered into three consecutive protocols. Patients undergoing salvage surgery after failure of chemotherapy ± radiotherapy and follow-up >5 years were considered for study. Variables related to the patient, to treatment, and to the surgical specimen were compared using the log-rank test in patients who achieved and failed to achieve 5-year progression-free survival (5-yr PFS). Odds ratios (OR) and 95% confidence intervals (95% CI) were calculated for significant variables. Results: Of the 108 patients enrolled in the protocols, 33 (30.6%) underwent salvage surgery and 26 matched study criteria. Seventeen patients were disease-free after a median follow-up of 125 months (range 65.5–311.7 months), 5-yr PFS 65.4%. Nine events were registered after a median follow-up of 5.4 months (range 1.9–27.5 months). Among the variables assessed (Table), only an undifferentiated histology proved to be significantly associated with a poorer 5-yr PFS, whereas a tumor size above 5 cm in the removed specimen approached significance. The OR (95% CI) for failure of 5-yr PFS was 28 (2.4–326.8) and 8.3 (1.03–67.1), respectively. Conclusion: 5-yr PFS proved unrelated to excision margins of the surgical specimen, that is on whether there was evidence of microscopic residues left behind during surgery. These data suggest that the outcome is more influenced by the biological properties of the tumor. If small foci of differentiated cells are left behind, these probably do not compromise final prognosis. In our patients requiring salvage bladder-prostate surgery after failure of chemotherapy ± radiotherapy, long-term progression-free survival seemed unrelated to patient/tumor characteristics at presentation and preoperative management. Regarding the characteristics of the removed specimen, instead, an undifferentiated tumor histology and a diameter of the removed tumor >5 cm negatively influenced prognosis, whereas the presence of positive excision margins did not.       PFS >5 years n/N (%) p Variables at diagnosis Age at diagnosis <5 years 14/20 (70) 0.4 >5 years 3/6 (50) Gender Male 12/20 (60) 0.3 Female 5/6 (83) Histology on initial biopsy Embryonal 9/16 (56) 0.1 Botryoid 8/9 (89) Tumor location Prostate 4/7 (57) 0.6 Bladder 11/15 (73) Bladder-prostate 2/4 (50) Tumor size <5 cm 5/7 (71) 0.7 >5 cm 12/19 (63) T-stage T1 7/10 (70) 0.7 T2 10/16 (62.5) Treatment variables Treatment protocol RMS 88 5/7 (71.5) 0.5 RMS 96 4/8 (50) RMS 2005 6/8 (75) Tumor response at 9 weeks Complete response (CR) 0/1 (0) 0.4 Partial response (PR) > 2/3 9/13 (69) Minor response (MR) > 1/3 but < 2/3 4/7 (57) No response or stable disease (SD) < 1/3 4/4 (100) Preoperative radiotherapy No 8/12 (67) 1 Yes 9/14 (64) Pathology variables Tumor location on surgical specimen Prostate 5/8 (62.5) 0.1 Bladder 11/14 (78.5) Bladder-prostate 1/4 (25) Surgical margins Negative 7/12 (58) 0.1 Positive 7/8 (87.5) Diameter of tumor at the surgical specimen <5 cm 10/12 (83) 0.06 >5 cm 3/8 (37) Histological differentiation Differentiated 11/13 (84.5) 0.002 Undifferentiated 1/7 (14) Myxoid 3/4 (75)